Evaluation of the effect of a resorbable membrane on the closure of palatal fistulas - Wang, Yufeng; Yang, Fangling; Liu, Weilong; Fan, Xiaofen; Lu, Yong (Frontiers in Surgery, 2023)
Purpose A palatal fistula following the closure of palatal clefts remains a difficult clinical complication. Surgical treatment of fistulas is often complicated, with high recurrence rates. We present our results of fistula closure augmented with GTR, a resorbable membrane designed to promote guided tissue regeneration. Methods We reviewed the records of 75 patients operated on between 2008 and 2022 for closure of the palatal fistula. The patients included 24 who underwent fistula closure augmented with GTR and 51 who underwent fistula closure with other techniques. We reviewed the age at surgery, sex, fistula location, and outcome. Operation success was defined as an asymptomatic patient with a healed fistula on clinical examination. Results The overall fistula closure rate was 79.1% in the GTR group and 76.5% in the non-GTR group(p = 0.79). Discussion The success rate of fistula closure in the GTR group is comparable to that in the non-GTR group in this study. An additional advantage is that this procedure does not require harvesting any autologous tissue and reduces tissue damage in the long term.